Akulturasi Budaya Arsitektur Masjid Sendang Duwur - siswayanti, Novita (Buletin Al-Turas, 2018)
Mosque of Sendang Duwur is broadcasting cultural heritage Sunan Sendang Duwur acculturated with the architectural vernacular of traditional Javanese and Hindu culture. This paper uses research methods descriptive analysis by describing the components of the mosque as analysis and interpretation. So that encountered a form of acculturation appears in the Sendang Duwur mosque architecture of the building is typical Joglo Javanese building forms, which were disputed by the four pillar , mustaka on the roof of the mosque bertumpang three similar buildings Meru in Hindu, the arch-shaped mihrab mosque Kalamakara like a temple, a mosque pulpit carved Jepara florish and the lotus -shaped , arch -shaped monument mosque briefly remind clicking on the shape of the building in the complex kedathon kori the Hindu kingdom. In the foyer there is candrasengkala Javanese writing on a wooden board that reads: gurhaning sarira tirta hayu ( 1483 S = 1561 AD)---Masjid Sendang Duwur adalah jejak peninggalan dakwah kultural Sunan Sendang Duwur yang gaya aristekturnya berakulturasi antara vernacular tradisi Jawa dengan Hindu.Artikel ini menggunakan metode penelitian deskripsi analisis dengan mendeskripsikan komponen-komponen masjid kemudian dianalisis dan diinterpretasikan. Dalam kajian ini ditemukan bahwa Masjid Sendang Duwur berarsitektur Joglo dengan empat soko guru yang menyanggah bangunan masjid merepresentasikan bangunan khas vulnacular daerah Jawa. Mustaka pada atap masjid bertumpang tiga mirip meru pada bangunan Hindu, mihrab masjid yang berbentuk lengkungan kalamakara seperti candi, mimbar masjid berukiran Jepara berbentuk florish dan bunga teratai, gapura masjid berbentuk tugu bentar mengingatkan pada bentuk bangunan kori pada kedathon di komplek Kerajaan Hindu. Pada serambi terdapat candrasengkala tulisan Jawa pada sebuah papan kayu yang berbunyi:gurhaning sarira tirta hayu (1483 S=1561 M).